Alat Bermain dan Bentuk Permainan Yang Merangsang Berkembangnya Kreativitas Pada Anak - Umaroh, Fina Lutvica; Putro, Khamim Zarkasih (GENIUS: Indonesian Journal of Early Childhood Education, 2021)
One aspect of development in early childhood that needs to be considered by teachers and parents is the creativity of children. The development of early childhood creativity is very important to note, because at this age, children are able to create something according to their wishes and imagination through objects around them. Children naturally have the potential for creativity, therefore children need activities that can encourage children's creativity. It can be seen from the importance of providing play tools and playing conditions that are right for children to encourage the development of creativity in children. This study aims to determine the tools and forms of play that stimulate the development of creativity in children. The research method used is the library method. This study explains that learning through play in early childhood is very important to encourage all aspects of child development. Children's learning facilities are through play activities, so the child's world is the world of play. Playing activities are very important to develop children's creativity, because through imaginative experiences, children are able to produce new and progressive perceptions, so that by doing play activities, children are able to grow their creativity. It is important for teachers and parents to know several types of playing tools and forms of play that can stimulate the development of creativity in children. Because by providing the right form of stimulation to children, the development of children's creativity can develop optimally.One aspect of development in early childhood that needs to be considered by teachers and parents is the creativity of children. The development of early childhood creativity is very important to note, because at this age, children are able to create something according to their wishes and imagination through objects around them. Children naturally have the potential for creativity, therefore children need activities that can encourage children's creativity. It can be seen from the importance of providing play tools and playing conditions that are right for children to encourage the development of creativity in children. This study aims to determine the tools and forms of play that stimulate the development of creativity in children. The research method used is the library method. This study explains that learning through play in early childhood is very important to encourage all aspects of child development. Children's learning facilities are through play activities, so the child's world is the world of play. Playing activities are very important to develop children's creativity, because through imaginative experiences, children are able to produce new and progressive perceptions, so that by doing play activities, children are able to grow their creativity. It is important for teachers and parents to know several types of playing tools and forms of play that can stimulate the development of creativity in children. Because by providing the right form of stimulation to children, the development of children's creativity can develop optimally.